1977
DOI: 10.1111/j.1365-2389.1977.tb02252.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Soil Organic Sulphur Fractions Due to the Long Term Cultivation of Soils

Abstract: The amount and chemical nature of soil organic sulphur was determined in several pairs of soils taken from long-term pasture and adjacent, continuously cultivated sites. Similar determinations were also carried out on organic matter extracts obtained from the soils. The lower levels of sulphur in the arable soils compared with pasture soils were assumed to have resulted from the mineralisation of organic matter brought about by cultivation. Losses of sulphur caused by this mineralisation were found to occur in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
1
3

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 7 publications
7
21
1
3
Order By: Relevance
“…According to this table, total organic S in bulk soils of the native grassland sites ranged from 194 to 853 mg kg À 1 soil, with an average of 441 mg kg À 1 soil ( Table 2, the Arvada site is excluded), while the concentration of organic S in the cultivated soils varied from 135 to 489 mg kg À 1 soil, the average being 300 mg kg À 1 soil. These results also indicated that organic S was the predominant form of soil S in the Great Plains comprising on the average 96% of the total soil S. The concentration of total SOS reported in this study falls within the range reported for temperate soils by Tabatabai and Bremner (1972), Neptune et al (1975), McLaren and Swift (1977) and Eriksen (1997). However, it is considerably lower than the values reported for humid and sub-humid tropical soils by Stanko-Golden and Fitzgerald (1991), Lehmann et al (2001) Solomon et al (2001) and Mö ller et al (2002).…”
Section: Organic S Forms In the Bulk Soils And Size Separates Of The supporting
confidence: 79%
See 3 more Smart Citations
“…According to this table, total organic S in bulk soils of the native grassland sites ranged from 194 to 853 mg kg À 1 soil, with an average of 441 mg kg À 1 soil ( Table 2, the Arvada site is excluded), while the concentration of organic S in the cultivated soils varied from 135 to 489 mg kg À 1 soil, the average being 300 mg kg À 1 soil. These results also indicated that organic S was the predominant form of soil S in the Great Plains comprising on the average 96% of the total soil S. The concentration of total SOS reported in this study falls within the range reported for temperate soils by Tabatabai and Bremner (1972), Neptune et al (1975), McLaren and Swift (1977) and Eriksen (1997). However, it is considerably lower than the values reported for humid and sub-humid tropical soils by Stanko-Golden and Fitzgerald (1991), Lehmann et al (2001) Solomon et al (2001) and Mö ller et al (2002).…”
Section: Organic S Forms In the Bulk Soils And Size Separates Of The supporting
confidence: 79%
“…These results concur positively with the suggestions of Lowe (1964), McLaren et al (1985), Schindler and Mitchell (1987) and Zhao et al (1996) that ester-SO 4 S can be stabilized independent of the main moiety of organic matter, may represents slightly more labile organic S fraction that can serves as a readily available S pool through biochemical mineralization process. In contrast to these findings, however, other studies using incubation and field experiments (Freney et al, 1975;McLaren and Swift, 1977;Ghani et al, 1991;Solomon et al, 2001;Mö ller et al, 2002) indicated that relatively larger proportion of SOS loss following land-use changes occurs from C-bonded S than ester-SO 4 S and stated that this organic S fraction represents the major source of mineralizable S in soils supporting the suggestion by McGill and Cole (1981). This view was also supported by our previous investigation using S XANES spectroscopy where Cbonded S (SOS in highly reduced and intermediate oxidation states) forms seems to represent the more labile forms of SOS compounds compared to ester-SO 4 S (SOS in highly oxidized states) forms and the dynamics of organic S was primarily driven by SOC turnover (Solomon et al, 2003(Solomon et al, , 2005.…”
Section: Effects Of Cultivation On Organic S Forms In Bulk Soils and mentioning
confidence: 54%
See 2 more Smart Citations
“…The decline in soil inorganic P and organic S after the cessation of superphosphate fertiliser could be attributed to the desorption of inorganic P from soil colloids (Syers & Iskander 1981) and the mineralisation of soil organic S (McLachlan 1975;McLaren & Swift 1977). This mobilisation of soil P and S reserves could be the main contributing factor in sustaining pasture production and herbage uptake of P and S in both the 376 and 564 kg/ha residual treatments above the unfertilised control.…”
Section: Discussionmentioning
confidence: 99%